Obtaining of Alumino-Matrix Alloys Al-Zr, Al-Zr-W by SHS-Metallurgy Method. (2019) - Gostishchev, Victor; Kim, Eugenie; Ri, Ernst
Abstract: The paper considers conditions for the synthesis of Al-Zr and Al-Zr-W alloys under aluminothermic reduction of zirconium oxide or mineral zirconium concentrate, baddeleyite. The alloys obtained are identified as aluminomatrix basing on the results of element and X-ray phase analysis. It is shown that the alloy synthesized from baddeleyite concentrate contains small amounts of impurities of silicon and oxygen (0, 5 % by weight). It is established that the alloys have a composite structure: inclusions of intermetallides Al 3 Zr and Al 4 W are distributed in the aluminum matrix, and they have the increased microhardness (7.9 and 4.5 GPa).